Metode Wafa dalam Pembelajaran Al-qur'an di Sekolah Alam TKIT Ar-Royyan Pegambiran, Padang - Sari, Ika Mutiara; Wirman, Asdi (Indonesian Journal of Islamic Early Childhood Education, 2019)
The research objective was to study the implementation of the Wafa method in Al-quran learning at the TKIT Ar-Royyan School of Nature. The Wafa method is an Al-quran learning method by maximizing the functions of the right brain without overriding the left brain which is combined in an interesting and fun way. The characteristic of Wafa's method is to read Al-quran with the strains of the hijaz and learning programs using movements that are in accordance with the verse translation. TKIT Ar-Royyan Nature School is a school that uses the Wafa method. The Wafa method is applied within a 5-year transfer period, previously using the Iqra 'method. The type of research used is descriptive qualitative research. Data collection techniques consist of observation, interviews, documentation. Data analysis techniques used since formulating data, explaining problems before going to the field and continuing to finish the research results. The technique of validating data uses triangulation techniques. The results of the study found that the implementation of the Wafa method used 5P, namely opening, meeting, meeting, meeting. The steps for implementing the Wafa method learning can be applied face to face for ± 60 minutes according to the mastery of the teacher.